2005
DOI: 10.5144/0256-4947.2005.283
|View full text |Cite
|
Sign up to set email alerts
|

Serum resistin, adiposity and insulin resistance in Saudi women with type 2 diabetes mellitus

Abstract: BACKGROUNDThe role of adipocyte hormones in modulating insulin sensitivity and glucose tolerance are of increasing interest and importance in studies of type 2 diabetes mellitus. Recently a unique signaling molecule, resistin, has been proposed as playing a role in the pathogenesis of obesity-related insulin resistance, but its relevance to human diabetes remains uncertain. Therefore, we assessed the relationship between serum resistin concentrations and insulin resistance in lean, overweight and obese (OW/OB)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 28 publications
3
29
0
2
Order By: Relevance
“…Several studies showed that increased resistin in T2D was not associated with markers of insulin resistance [22,23,55]. In contrast, Silha [56] as well as Al Harithy [57] reported the same results as we did, of a significant correlation between elevated resistin levels and the HOMA-IR index in patients with T2D. Our results show that in T2D patients elevated resistin levels are more related to the diabetic state and IR than to total adiposity.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies showed that increased resistin in T2D was not associated with markers of insulin resistance [22,23,55]. In contrast, Silha [56] as well as Al Harithy [57] reported the same results as we did, of a significant correlation between elevated resistin levels and the HOMA-IR index in patients with T2D. Our results show that in T2D patients elevated resistin levels are more related to the diabetic state and IR than to total adiposity.…”
Section: Resultsmentioning
confidence: 99%
“…Apart from the diabetes, leptin also affects a variety of other physiological functions, including fertility, bone metabolism, and immune responses [113]. …”
Section: Introductionmentioning
confidence: 99%
“…Initial experimental studies in rodents pointed to an important role of resistin as a mediator of obesity-associated insulin resistance (22). While the majority of recent animal studies further supports this hypothesis, the physiological relevance of resistin for obesity-related conditions in humans remains controversial (4), and inference from most human studies was limited by cross-sectional design and small sample size (2333). …”
Section: Introductionmentioning
confidence: 99%